2013
DOI: 10.1007/s00402-013-1838-y
|View full text |Cite
|
Sign up to set email alerts
|

Total knee replacement following high tibial osteotomy versus total knee replacement without high tibial osteotomy: a systematic review and meta analysis

Abstract: Systematic review and meta analysis suggested that TKR following HTO provides similar outcomes as compared to TKR without previous HTO. Therefore, a previous HTO does not negatively influence a future TKR, though the conversion process of HTO to TKR is technically challenging. Systematic review also identified paucity in prospective and long term studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 19 publications
0
29
0
1
Order By: Relevance
“…52 Although there is con cern regarding increased complexity of total knee replacement following high tibial osteotomy, metaanalysis of published data suggests no differences in functional outcomes, survivor ship or complication rates when total knee replacement is performed in those with or without previous high tibial osteotomy. 53…”
Section: Tibial Osteotomymentioning
confidence: 99%
“…52 Although there is con cern regarding increased complexity of total knee replacement following high tibial osteotomy, metaanalysis of published data suggests no differences in functional outcomes, survivor ship or complication rates when total knee replacement is performed in those with or without previous high tibial osteotomy. 53…”
Section: Tibial Osteotomymentioning
confidence: 99%
“…There have been conflicting reports regarding this issue. A previous meta-analysis, consisting of 11 studies with 421 HTO-TKAs and 1749 primary TKAs found no significant differences in terms of revision, complications and functional outcome [12]. In our analysis, 15 studies with 4646 HTO-TKAs and 140,074 primary TKAs were included, the substantial increase of sample size may help to investigate low-incidence event such as revision.…”
Section: Discussionmentioning
confidence: 82%
“…A previous meta-analysis published in 2013 reported similar outcomes between TKA following HTO and primary TKA in terms of survival and perioperative complications [12]. Most studies included in the previous metaanalysis investigated cohorts of small sample size.…”
Section: Introductionmentioning
confidence: 95%
“…There were no statistically 20 However, many studies have demonstrated that HTO and DFO can be used without impacting revision TKA outcomes. [21][22][23][24][25] Despite this, longitudinal trends suggest a decline in the use of HTO and DFO in the United States and in favor of unicompartmental or TKA. 19,[26][27][28] This is in contrast to countries such as Japan 29 and Korea 30 that demonstrated increased usage of HTO and DFO for knee OA.…”
Section: Resultsmentioning
confidence: 99%